Innovation of M-Health-Based Prosa-Hi Application for Early Detection of Child Growth and Development - Sunarsih, Tri; Astuti, Endah Puji; Purnamaningsih, Nur'Aini; Suwarno; Syah, Muhammad Erwan; Shanti, Elvika Fit Ari; Habibi, Muhammad; Kharisma; Rukmi, Dwi Kartika (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2023)
The development of technology has advanced digital and intelligent transformation, including in the child health. This study was conducted to implement the PROSA-HI Application to detect child growth early. The research method uses the sequential mix methods. The PROSA-HI Application will be implemented in Nogotirto Village from August 2022 to November 2022. The data collection techniques in this study include Observation, Interviews, and questionnaires with mothers with toddlers using the User Acceptance Test (UAT) questionnaire of 291 mothers under five. Analysis by univariate analysis. Testing the PROSA-HI Application with a user acceptance test showed an average of 89.0%, so it can be concluded that the usability rate of the PROSA-HI application system based on user perception is considered feasible to implement. The PROSA-HI Application can effectively monitor children's health, growth, and development, positively impacting parents and health workers.